GeoPortale OpenData del Comune di Firenze: progettazione, implementazione e lessons learned - Castagnoli, Enrico; Giannecchini, Simone; Ricci, Leonardo (GEOmedia, 2012)
La volontà dei vertici del Comune di Firenze di aprire i propri dati alla cittadinanza in linea con le recenti iniziative OpenData ha creato la necessità di mettere in piedi una infrastruttura dedicata che andasse da un lato incontro alle esigenze del pubblico ma che dall'altro lato si andasse ad integrare in modo semplice e trasparente con la infrastruttura esistente del SIT. La decisione di basarsi interamente su software Open Source per i nuovi componenti ha creato ulteriori incognite su questa nuova implementazione. Scopo di questo articolo è descrivere non solo i componenti utilizzati ed il lavoro di integrazione svolto, ma anche le linee guida e le policy seguite durante la vita del progetto che sono risultate fondamentali per la sua buona riuscita. The township of Florence has been the first one in Italy to fully adhere to the OpenData initiative by releasing many of its own data through open and permissive licenses with the objective of increasing transparency of its procedure as well as to boost awareness and participation from the citizenship; last but not least the goal of supporting and encouraging developers' creativity with creating innovative applications exploiting all the newly available data was also an important driver especially in these times of harsh economic conditions. The decision makers of the Florence SIT office, responsible for the creation of the infrastructure for supporting the OpenData initiative, have decided to enhance the existing, consolidated infrastructure using only Open Source software and therefore they decide to hire renowned GeoSpatial Open Source experts from the GeoSolutions Italian company to help them with the design and implementation as well as to ensure the presence of competent commercial support for the chosen solutions and to receive the necessary training on the job to guarantee the sustainability of the infrastructure in the long term. This article firstly introduce the existing situation at the time the design of the new infrastructure was started as well as the initial objectives. Afterwards we introduce and dissect the work performed to actually implement the changes to the infrastructure, providing detailed information on the building blocks employed as well as on the policies followed. Eventually, we introduce the next steps to be implemented for the infrastructure.